2019
DOI: 10.1016/j.ijso.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pelvic resection from malignant pelvic tumors. A case series

Abstract: Introduction: Malignant pelvic tumors also tend to present late and therefore pose a major challenge for orthopedic oncologists because of the large tumor size, local extension, and complex anatomy with proximity to major neurovascular structures and intestinal and urinary tracts. Method: We evaluated the oncologic, functional outcome and complications following internal hemipelvectomy in a consecutive series of patients with malignant muculoskeletal tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Joel et al Also concluded that although the mortality is relatively low in hemipelvectomy group, the morbidity is high including wound infection and flapnecrosis. 1,[5][6][7][8][9] Despite of difficulty in obtaining negative margin of resection, limb salvage surgery for pelvic tumors can improve patient's quality of life by reducing psychological trauma and physical disability. Limb salvage surgery by pelvic resections are challenging procedure to manage pelvic malignancies, severe trauma, and infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Joel et al Also concluded that although the mortality is relatively low in hemipelvectomy group, the morbidity is high including wound infection and flapnecrosis. 1,[5][6][7][8][9] Despite of difficulty in obtaining negative margin of resection, limb salvage surgery for pelvic tumors can improve patient's quality of life by reducing psychological trauma and physical disability. Limb salvage surgery by pelvic resections are challenging procedure to manage pelvic malignancies, severe trauma, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure includes the resection of the involved hemipelvis which further divided into four types according to Enneking and Dunham: type I involves the ilium; type II involves the acetabulum, type III involves the ischium and pubic rami, and type IV involves sacrum. 1,[5][6][7]10,11 In our patient, the tumor was extended from ilium, ischium to the ipsilateral pubic bones owe decided to perform wide excision involving those bone by pelvic resection type I/II/III. Pelvic complex structure makes the pelvic resection is such a challenging and technically demanding surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations